Effect of the decrease of Pb concentration on the properties of pentarnary mixed-halide perovskites CsPb8-xSnxIBr2 and CsPb8-xSnxI2Br (1≤x≤7) for solar-cell applications: A DFT study. (February 2022) - Ahmed, Hussain; Jalil, Abdul; Ilyas, Syed Zafar; Agathopoulos, Simeon; Ahmed, Ishaq; Zhao, Tingkai; Dahshan, A.
Abstract: In order to investigate the possibility of producing novel perovskite materials for fabricating solar cells with low toxicity, the influence of Sn substitution for Pb on the structural, electronic, and optical properties of the pentarnary compounds CsPb8-x Snx IBr2 and CsPb8-x Snx I2 Br (for 1 ≤ x ≤ 7) was investigated by density functional theory (DFT) calculations using the GGA-PBE approximation. The predicted structure of these new pentarnary materials is cubic. Their optical absorption coefficient is predicted to be in the range of 10 5  cm −1, which is a good match with that of the Sn-free CsPbIBr2 and CsPbI2 Br compounds. The increase in Pb concentration causes an increase in the bandgap as well as in the optical absorption coefficient, which reveal the key role of Pb in perovskite solar cells. The compounds with the highest Pb concentration, CsPb7 SnIBr2 and CsPb7 SnI2 Br, exhibited a promising bandgap of 1.31 and 1.29 eV, respectively, which is close to the Shockley-Queisser bandgap limit that is the best for solar-cell applications. The above properties, in conjunction with their relatively easy synthesis process, qualify these new predicted materials for being included in the family of the mixed-halide perovskites. Highlights: The influence of Sn substitution for Pb on the structural, electronic, and optical properties of pentarnary mixed halide perovskites is investigated by DFT calculations. The pentarnary mixed halide perovskites possesses cubic structure. The optical absorption coefficients are in the range of 10 5  cm −1 . The compounds with the highest Pb concentration exhibited bandgap close to the Shockley-Queisser limit. Increase in Pb concentration cause to increase bandgaps as well as absorption coefficients.